Answers

2014-11-26T16:18:26+05:30
solve for x : 2x - 3 ( 2x +1 ) = 9
solution: 
            2x - 6x  - 3 = 9
                 -4x        = 9 + 3 
                 - 4x       =  12 
                     x       = 12 / -4
                     x       = -12 /4 
                     x       = -3 
1 4 1
2014-11-26T16:32:58+05:30
2x-3[2x+1]=9
=2x-6x-3=9 
=>    -4x-12=0
take 2 common from above equation..............
   ==>      -2x-6=0

    =>       -x=6÷2
    ==>      x=-3         
                            plz ,mark it best:--}


0